2009
DOI: 10.2139/ssrn.1372402
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion of it in Higher Education: Publishing Productivity of Academic Life Scientists

Abstract: This study investigates widening access to the Internet and other advancements in IT across institutions of higher education and how these advances have affected the publishing productivity of academic life scientists. What distinguishes this study is that institutional IT access is measured across a wide range of institutions and multiple IT indicators are considered: 1) the adoption of BITNET; 2) the registration of domain names (DNS); 3) the availability of the electronic journal database, JSTOR; and 4) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…However, two factors augur against this quick conclusion: first, most biotechnological information is not tacit, so it will be relatively easy to communicate across long distances. Second, biotechnology patenting has occurred largely during a period when electronic international and inter-regional communication has been increasingly effective and affordable, so once again we might expect less localization of knowledge spillovers (Feldman 1999;Winkler et al 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…However, two factors augur against this quick conclusion: first, most biotechnological information is not tacit, so it will be relatively easy to communicate across long distances. Second, biotechnology patenting has occurred largely during a period when electronic international and inter-regional communication has been increasingly effective and affordable, so once again we might expect less localization of knowledge spillovers (Feldman 1999;Winkler et al 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Narrower expertise, in turn, leads to an increased reliance on teamwork for discovery. Third, the rapid spread of connectivity, which began in the early 1980s with the adoption of BITNET by a number of universities and accelerated in the early 1990s with the diffusion of the Internet, has decreased the costs of collaboration across institutions (Agrawal and Goldfarb 2008;Winkler, Levin, and Stephan 2008). Another factor that fosters collaboration is the vast amount of data that is becoming available, such as that from the Human Genome Project (and the associated GenBank database).…”
Section: The Importance Of Teamsmentioning
confidence: 99%
“…A number of past studies have focused the impact of implementing Human Resource Information Systems (HRIS) on the performance of employee and organization (Hussain et al, Mithas et al, 2011;Kundu andKadian, 2012, Stone et al, 2015;Bussler and Davis, 2002;Bondarouka et al, 2017, Wibawa et al, 2018. Also, authors of several past studies (Allen, 1986;Winkler et al, 2010;Cette et al, 2017;Edquist and Henrekson, 2017;Pieri et al, 2017) have concentrated on the role of Internet Communication Technologies (ICT) in fulfilling Human Resource Management (HRM) objectives, namely, performance assessment and manpower recruitment. Hussain et al (2007) have studied the impact of HRIS on the human resource (HR) professionals in small-, medium-and large-scale enterprises and found that the HRIS are used extensively by all of them.…”
Section: Information Management Systems and Internet Communication Technologies (Ict) For Hrmmentioning
confidence: 99%